A Cultural Intelligence Study of British Manners in Sunday Roast and Silent Guidelines - Yoan Natalia Matahelumual; Devansa Riski Indrasara; Mayo Hadi Wibowo; Elis Yuliana; Agung Budi Kurniawan (Universitas Tidar, 2025)
With an eye towards Aisha, an exchange student negotiating British table etiquette at a traditional Sunday roast, this research investigates the evolution of cultural intelligence via a narrative text called “Sunday Roast and Silent Guidelines”. With the four-dimensional Cultural Intelligence (CQ) framework namely cognitive, metacognitive, motivating, and behavioral which the study follows Aisha's acquisition of fresh cultural knowledge, considers past presumptions, modifies her behavior, and maintains curiosity in the face of uncertainty. Based on the results, especially in educational environments, personal stories seem to be low-risk yet powerful instruments for improving intercultural competency. Emotionally interesting events enable students to find underlying cultural values and react correctly to foreign social signals. This paper supports the use of narrative-based techniques in English and multicultural classes. These tales not only raise understanding of different cultures but also help pupils to be more flexible and sympathetic-qualities that are vital in a society going global. Moreover, narrative books let students absorb multicultural lessons by means of relevant characters and scenarios. Seeing Aisha's quiet learning approach helps teachers to better grasp how their students view cross-cultural encounters. In the end, this method promotes critical thinking and gets students ready for significant participation in many cultural settings.